Towards Online Visualization and Interactive Monitoring of Real-Time CFD Simulations on Commodity Hardware - Nils Koliha (Computation, 2015)
Real-time rendering in the realm of computational fluid dynamics (CFD) in particular and scientific high performance computing (HPC) in general is a comparably young field of research, as the complexity of most problems with practical relevance is too high for a real-time numerical simulation. However, recent advances in HPC and the development of very efficient numerical techniques allow running first optimized numerical simulations in or near real-time, which in return requires integrated and optimized visualization techniques that do not affect performance. In this contribution, we present concepts, implementation details and several application examples of a minimally-invasive, efficient visualization tool for the interactive monitoring of 2D and 3D turbulent flow simulations on commodity hardware. The numerical simulations are conducted with ELBE, an efficient lattice Boltzmann environment based on NVIDIA CUDA (Compute Unified Device Architecture), which provides optimized numerical kernels for 2D and 3D computational fluid dynamics with fluid-structure interactions and turbulence.